Alteration of relations in marriage and problem of ethnocultural traditions’ fixity - Goncharova, Galina S. (The New Research of Tuva, 2010)
Article reveals results of wide-scale sociological researches conducted in 2005-2007 by the staff of Ethnosocial research sector of Russian Academy of Sciences Siberian Branch Institute for Philosophy and Law. Researches were devoted to alteration in views for family and marriage relations in republics of Tyva, Khakassia, Altai, Kalmykia and Sakha (Yakutia).
Keywords: family; traditions; generations; family values; Siberia; regions; Tuva; Khakassia; Altai; Kalmykia; Yakutia; RAS SB; sociology